Occurrence of Myzus persicae on chryzanthemum - Oliveira, Alda M. de; Cruz, Celma de A. da; Ferreira, Levi (Pesquisa Agropecuaria Brasileira, 2014)
The green peach aphid Myzus persicae Sulzer, 1776 (Homoptera: Aphididae) was first found as a Chrysanthemum morifolium crop pest in Barbacena, state of Minas Gerais, Brazil. Identification was done on apterous and alate viviparae females collected in May of 1986. Aphid population was found damaging stems and buds of Chrysanthemum plants.